2016
DOI: 10.3892/mmr.2016.5231
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in pregnancy complications (Review)

Abstract: Telomeres are specific DNA regions positioned at the ends of chromosomes and composed of functional non-coding repeats. Upon cell division, the telomeres decrease in length by a preordained amount. When the telomeres become critically short, cells lose the ability to divide and enter a specific functioning mode designated as 'cellular senescence'. However, human tissues express an enzyme that deters the shrinking of the telomeres, the telomerase. Due to its ability to maintain telomere length, the telomerase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 79 publications
0
28
0
1
Order By: Relevance
“…We used multiple linear regression to test for associations between gravidity and telomere length (adjusted for age and race). Because the groups had different years of education and proportions of women with gestational diabetes and preterm births and all these factors have been associated with telomere length in earlier investigations [ 15 , 16 , 18 ], we performed an ANCOVA to determine whether years of education, preterm birth, or gestational diabetes affected the association of telomere length and gravidity group. A chi-square test was performed to determine whether there was a difference in prevalence of high-risk, short telomere length, defined as the lowest quartile of telomere length (≤ 0.844) between groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used multiple linear regression to test for associations between gravidity and telomere length (adjusted for age and race). Because the groups had different years of education and proportions of women with gestational diabetes and preterm births and all these factors have been associated with telomere length in earlier investigations [ 15 , 16 , 18 ], we performed an ANCOVA to determine whether years of education, preterm birth, or gestational diabetes affected the association of telomere length and gravidity group. A chi-square test was performed to determine whether there was a difference in prevalence of high-risk, short telomere length, defined as the lowest quartile of telomere length (≤ 0.844) between groups.…”
Section: Methodsmentioning
confidence: 99%
“…We repeated all analyses stratified by race, as race has been shown to influence telomere length in women [ 18 ]. We also tested whether women with gestational diabetes or preterm birth had shorter telomeres than women without these complications in our sample because telomerase activity has been shown to be acutely affected by complications of pregnancy [ 15 ]. Next, we conducted two sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TL and telomerase activity are strongly associated with human health as they have been linked to several age-related diseases, such as cancer, cardiovascular disease (CAD), diabetes, rheumatoid arthritis and psychiatric disorders (34)(35)(36)(37)(38). Moreover, previous studies have suggested that female human fertility decreases with an increased maternal age and that various adverse factors, including reduced telomerase activity, can contribute to age-associated infertility in women (39,40). Furthermore, Vakonaki et al recently demonstrated the existence of a link between TL and drug abuse, which ultimately results in premature biological aging (41).…”
Section: Role Of Telomeres and Telomerase In Agingmentioning
confidence: 99%
“…The adverse intrauterine environment during pregnancy is caused by factors like psychosocial risk issues, lack of social support, low socioeconomic status, and childhood trauma [19,20]. Association to the telomere and fetal programming and gene expression modifications has also been found linked with pre-eclampsia [21], intrauterine growth restriction (IUGR) [22], oxidative and nitrosative stress, and hypoxia [23,24].…”
Section: Introductionmentioning
confidence: 99%